Application of Calm Pregnancy Based on Artificial Intelligence as an Early Anxiety Detection and Recommendations for Pregnant Women - Nisa Annisa Arfiyanti; Melyana Nurul Widyawati; Kurnianingsih Kurnianingsih (Jurnal Keperawatan Silampari, 2023)
This research aims to develop and test the Calm Pregnant application for early detection and recommendations for anxiety. The method used in this research uses two stages. The first stage is research and development (R&D), which aims to develop products whose quality will be tested. The trial results show that the Calm Pregnancy Application is relevant as a medium in speeding up early detection of anxiety by a difference of 172.65 seconds, speeding up the provision of recommendations to pregnant women by a difference of 250.79 seconds, and being able to get feedback from midwives directly. The Calm Pregnancy application has been proven to be effective for use by pregnant women, with an effectiveness rate of 90.5% (very high). The conclusion resulted in a product in the form of the Calm Pregnancy media application, which was proven to be effective in carrying out early detection and providing recommendations to pregnant women, as well as the Calm Pregnancy application, which has advanced features based on artificial intelligence. The difference in speed of time and provision of recommendations in early detection of anxiety is statistically significant. Keywords: Early Detection, Human in the Loop, Anxiety